2010
DOI: 10.1177/1074248410387606
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Antagonists in Heart Failure

Abstract: Aldosterone antagonists represented by nonselective spironolactone and mineralocorticoid-selective eplerenone are approved for treatment of symptomatic heart failure with reduced systolic function. Their cardioprotective, antifibrotic, and antiarrhythmic effects have been proven in animal experiments, and their effects on morbidity and mortality have been demonstrated in randomized clinical trials. Yet, they remain the most underutilized of all classes of medications for heart failure, primarily because of fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 106 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…For this reason, the groups were balanced for numbers of CKCS by the minimization method; the trial was not, therefore, truly randomized. However, mineralocorticoid receptor antagonists have been shown to be beneficial in human patients, regardless of plasma aldosterone concentrations [29]. Large studies that allow for subanalyses according to breed are necessary to investigate whether breed-specific effects of spironolactone exist.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the groups were balanced for numbers of CKCS by the minimization method; the trial was not, therefore, truly randomized. However, mineralocorticoid receptor antagonists have been shown to be beneficial in human patients, regardless of plasma aldosterone concentrations [29]. Large studies that allow for subanalyses according to breed are necessary to investigate whether breed-specific effects of spironolactone exist.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious impact of aldosterone in patients with heart failure and systolic left ventricular dysfunction is now well demonstrated. [1][2][3] Conversely, the deleterious role of high aldosterone levels, associated with sudden cardiac death (SCD) and ventricular arrhythmias (VAs) occurrence, at the acute phase of ST-segment elevation myocardial infarction (STEMI), has been more recently highlighted. 4 Therefore, the possible benefit of mineralocorticoid receptor (MR) blockade early after STEMI onset and even in preserved systolic left ventricular function has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 If Ucn2 is likewise to find a place in the treatment of HF, it should ideally enhance any beneficial effects of MRAs while reducing-or at least not exacerbating-the adverse consequences of such therapy. In the present study in experimental HF, we have demonstrated for the first time that Ucn2, when added to the MRA, CA, improved hemodynamic, hormone, electrolyte, and renal indices.…”
Section: Discussionmentioning
confidence: 99%
“…Direct blockade of aldosterone's actions with MR antagonists (MRAs) such as spironolactone and eplerenone, now recognized as a third class of RAAS inhibitor, has been shown in a number of large interventional clinical trials to reduce morbidity and mortality in patients with HF. [3][4][5] However, although MRAs are now an important accessory in our pharmaceutical management of HF, they remain the most underused of all medications, largely because of the fear of hyperkalemia, 6 hypotension, and renal impairment. 7 Urocortin 2 (Ucn2) belongs to a group of peptides (Ucn1-3) sharing structural similarities with the hypothalamic hormone corticotropin-releasing factor (CRF).…”
mentioning
confidence: 99%